Vegetable Oil Economic Diplomacy as an Instrument of Indonesian Foreign Policy - Hutabarat, Leonard (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
The development of international politics due to the Russian-Ukrainian conflict has caused international political instability and pressure on agricultural products and the energy sector in the world. Indonesia's leading export commodity, under discriminatory pressure from the European Union, also has economic implications due to the Russian-Ukrainian war. Disruption to the world's vegetable oil supply chains, the urgent need for food security, and the impact on achieving the goals of sustainable development that have been agreed upon so far make Indonesia seek to use the existing narrative through economic diplomacy. This condition is also related to Indonesia's vegetable oil diplomacy as one of the foreign policy instruments. Therefore, economic diplomacy regarding Indonesian vegetable oils is also part of Indonesia's national interest. This article uses qualitative methods with a descriptive-analytical type on how Indonesia uses the narrative of sustainable development issues in the context of Indonesian vegetable oils to achieve Sustainable Development Goals 2030, including instruments of economic diplomacy in realizing Indonesia's national interest in Indonesia's vegetable oil diplomacy. Keywords: economic diplomacy, Indonesia, foreign policy, vegetable oil, SDGs 2030 Perkembangan politik internasional akibat konflik Rusia-Ukraina telah menimbulkan dampak tidak hanya instabilitas politik internasional, namun juga tekanan terhadap komoditas produk pertanian maupun sektor energi di dunia. Komoditas ekspor unggulan Indonesia yang selama ini mendapatkan tekanan yang bersifat diskriminatif dari Uni Eropa juga memiliki implikasi ekonomi akibat terjadinya perang Rusia-Ukraina. Gangguan terhadap rantai pasok minyak nabati dunia dan sangat diperlukan tersedianya ketahanan pangan serta dampak terhadap pencapaian tujuan dari pembangunan berkelanjutan yang telah disepakati selama ini, menjadikan Indonesia berupaya menggunakan narasi yang ada melalui diplomasi ekonomi. Hal ini juga terkait dengan diplomasi minyak nabati Indonesia sebagai salah satu instrumen kebijakan luar negeri. Diplomasi ekonomi berkenaan dengan minyak nabati Indonesia juga merupakan bagian dari kepentingan nasional Indonesia. Artikel ini akan menjelaskan dengan metode kualitatif dengan jenis deskriptif analitis bagaimana Indonesia menggunakan narasi pembangunan berkelanjutan dalam konteks minyak nabati Indonesia guna mencapai Sustainable Development Goals 2030, termasuk instrumen diplomasi ekonomi dalam mewujudkan kepentingan nasional Indonesia dalam diplomasi minyak nabati Indonesia. Kata-kata Kunci: diplomasi ekonomi, Indonesia, kebijakan luar negeri, minyak nabati, SDGs 2030